Optimal approximation of fractional derivatives through discrete-time fractions using genetic algorithms - Machado, J. A. Tenreiro (2014)
This study addresses the optimization of rational fraction approximations for the discrete-time calculation of fractional derivatives. The article starts by analyzing the standard techniques based on Taylor series and Padé expansions. In a second phase the paper re-evaluates the problem in an optimization perspective by tacking advantage of the flexibility of the genetic algorithms.